Effect of Antiviral Therapy During Pregnancy on Natural Killer Cells in Pregnant Women With Chronic HBV Infection - Wang, Fuchuan; Xie, Si; Ran, Chongping; Hao, Hongxiao; Jiang, Tingting; Deng, Wen; Bi, Xiaoyue; Lin, Yanjie; Yang, Liu; Sun, Fangfang; Zeng, Zhan; Xie, Yao; et al. (Frontiers in Immunology, 2022)
Objective: To study the effect of antiviral therapy during pregnancy on the frequency of natural killer (NK) cells in peripheral blood of women with HBV DNA positive chronic hepatitis B (CHB). Method: In total 124 female subjects were divided into four groups: 11 healthy non-pregnant women (Normal group), 26 non-pregnant women in immune tolerance period of chronic hepatitis B virus (HBV) infection (CHB group), 41 pregnant CHB women without antiviral treatment during pregnancy (Untreated group), and 46 pregnant CHB women receiving antiviral treatment during pregnancy (Treated group). The frequency of NK cells in peripheral blood were detected by flow cytometry. Result: The frequency of NK cells in healthy women [15.30 (12.80, 18.40)] was higher than that in women with HBV infection, but there was no significant statistical difference (p=0.436). The frequency of NK cells in CHB group [10.60 (6.00, 18.30)] was higher than those in pregnant CHB women [Untreated: 6.90 (4.89, 10.04), P=0.001; Treated: 9.42 (6.55, 14.10), P=0.047]. The frequency of NK cells in treated group was significantly higher than that in untreated group (P = 0.019). The frequencies of NK cells, CD56bright NK cells and NKp46dim NK cells at 12 and 24 weeks postpartum in the untreated group were increased significantly than those before delivery. In treated group, the frequencies of NK cells, CD56bright NK cells, NKp46+ NK cells and NKp46dim NK cells were significantly increased at 6 and 12 weeks than those before delivery. The frequencies of NK cells and CD56bright NK cells postpartum were increased significantly in treated group than those in untreated group. The frequencies of CD56dim NK cells decreased significantly after delivery in treated than those in untreated patients. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) significantly increased after delivery than those before delivery. The results showed that the postpartum ALT level was weak positive correlated with NKp46high frequency (r=0.199) and was weak negative correlated with NKp46dim frequency (r= -0.199). Conclusion: Antiviral treatment during pregnancy could significantly increase the frequency of NK cells postpartum. Postpartum hepatitis may be related to the immune injury caused by change of NK cell frequency and HBV infection.